Development of an Experience-Based Interpersonal Communication Model: A Qualitative Study of Non-Professional Caregivers in Indonesian Mental Health Rehabilitation - Tita Azzahra Putri; Maulana Rezi Ramadhana (INJECT (Interdisciplinary Journal of Communication), 2026)
Interpersonal communication in non-clinical mental health rehabilitation is largely shaped by non-professional caregivers, yet existing therapeutic communication models emphasize clinical expertise and structured protocols. This study explores how experience-based relational practices emerge among Pramujiwa non-professional caregivers at Satpel Bina Laras Sakurjaya, Indonesia, through daily interactions with clients with mental disorders (ODGJ). Employing an intrinsic single-case qualitative design grounded in interpretivist and experiential learning perspectives, data were collected via unstructured interviews, participant observation, and document analysis with 10 key Pramujiwa informants, supporting staff, and an expert informant. Inductive thematic analysis identified four recurring interaction patterns: Initial Familiarization, Trust Negotiation, Daily Engagement, and Informal Continuity, which were synthesized into a three-phase conceptual model: Affectional, Adaptive, and Relationship Consolidation phases. Findings indicate that relational effectiveness is maintained through emotional attunement, situational adaptation, and continuity across everyday activities rather than formal clinical procedures. The Pramujiwa Interpersonal Relationship Model demonstrates that meaningful therapeutic-like communication can develop from sustained, context-sensitive experiential practice. The study highlights the significance of non-professional, experience-based caregiving for psychosocial stabilization and relational continuity in resource-limited rehabilitation contexts, offering theoretical and practical insights for enhancing interpersonal communication frameworks in non-clinical mental health care.